Adaptive Instructional Strategies for Mixed-Age Classrooms: Teaching Arabic to Heterogeneous Young Learners in Non-Formal Malaysian Settings - Nurbaiti Maulida Ramadhani; Siti Kholiza Nasution (Diwan Media Pustaka, 2026)
Teaching Arabic in non-formal international educational settings presents considerable pedagogical challenges, particularly when classrooms consist of learners with diverse age ranges, heterogeneous linguistic backgrounds, and varying levels of learning motivation. These conditions require adaptive instructional approaches that can accommodate students’ cognitive and emotional needs. Therefore, this study aims to analyze methodological barriers and formulate adaptive strategies for teaching Arabic in the International Teaching Program in Malaysia. The study focused on mixed-age classrooms comprising students aged 9–17 years with minimal Arabic language proficiency and fluctuating learning motivation. This research employed a qualitative approach using a Classroom Action Research design. Data were collected through participatory observation and analysis of the teacher’s daily reflective journals throughout the implementation of the program. The findings revealed that substantial cognitive differences among age groups and reduced physical stamina caused by the intensive daytime boarding school schedule constituted the primary instructional barriers. To address these challenges, four adaptive instructional strategies were implemented, namely psychological conditioning through educational-song based ice breaking activities, Game Based Learning supported by flaschcards, cross age peer tutoring, and instructional scaffolding through external code switching to Malay. Participatory observations and reflective journal entries indicated that these strategies transformed students’ participation from passive to active, promoted collaborative interaction between younger and older learners, fostered a more inclusive learning environment, and enhanced students’ understanding of foundational Arabic language concepts. These findings suggest that methodological flexibility, supported by adaptive and interactive instructional strategies, plays a crucial role in improving Arabic language learning in heterogeneous non-formal educational settings.